THE EFFECT OF SEMANTIC MAPPING STRATEGY ON STUDENTS’ SPEAKING ACHIEVEMENT IN SMP NEGERI 1 SEI SUKA - Liza Insyirah; Tjut Ernidawati (Universitas Negeri Medan, 2014)
This study aims to discover the effect of applying Semantic Mapping Strategy on students’ speaking achievement. It was conducted by using experimental research design. The population of this research was the eight (VIII) grade students of SMP Negeri 1 Sei Suka. The samples of the research were two classes which consisted of experimental and control group which were chosen by using random sampling technique. Thirty one students were taken as the samples in each class. The experimental group was taught by using Semantic Mapping Strategy, while the control group was taught without using Semantic Mapping Strategy. After analyzing the data, it was found that the value of tobserved was 3,12 with the degree of freedom (df)=60 at the level of significance p(0,05) = 2,000. It means that tobserved was higher than t-table (3,12>2,000). The result of this study showed that Semantic Mapping Strategy was significantly affect on students’ speaking achievement.